2011
DOI: 10.3354/dao02344
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a reverse transcription quantitative PCR for universal detection of viral hemorrhagic septicemia virus

Abstract: Viral hemorrhagic septicemia virus (VHSV) infects over 70 fish species inhabiting marine, brackish or freshwater environments throughout the Northern Hemisphere. Over its geographic range, 4 VHSV genotypes and multiple subtypes exist. Here, we describe the development and validation of a rapid, sensitive and specific real-time reverse transcription quantitative PCR assay (RT-qPCR) that amplifies sequence from representative isolates of all VHSV genotypes (I, II, III and IV). The pan-specific VHSV RT-qPCR assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 47 publications
(37 reference statements)
3
60
1
Order By: Relevance
“…Initial virus identity for isolates prior to 1998 was determined using a DNA probe (Batts et al 1993), while isolations post 1998 were confirmed via VHSV-specific reverse transcriptase polymerase chain reaction (RT-PCR) as described below. All BC VHSV isolates listed herein were cultured with the exception of the Pa cific Hake isolate which was detected via quantitative RT-PCR (RT-qPCR) (Garver et al 2011) and RT-PCR.…”
Section: Virus Isolation and Fish Lossesmentioning
confidence: 99%
“…Initial virus identity for isolates prior to 1998 was determined using a DNA probe (Batts et al 1993), while isolations post 1998 were confirmed via VHSV-specific reverse transcriptase polymerase chain reaction (RT-PCR) as described below. All BC VHSV isolates listed herein were cultured with the exception of the Pa cific Hake isolate which was detected via quantitative RT-PCR (RT-qPCR) (Garver et al 2011) and RT-PCR.…”
Section: Virus Isolation and Fish Lossesmentioning
confidence: 99%
“…For quality control purposes and to provide unambiguous definitions of positive and negative test results, both negative and positive controls should be included in each of the test runs. To show the needed information in this item, a description of the quality control samples used in a real-time RT-PCR validation study is presented in the example above (Garver et al 2011) and in Greer & Collins (2007). Authors should also specify whether or not internal and/or artificial controls are included in PCR assays to identify false-negative or falsepositive test results (Snow et al 2009, Purcell et al 2014, as well as the protocol for retesting such samples.…”
Section: Explanationmentioning
confidence: 99%
“…The challenge conditions, particularly the dose and strain of pathogen, should be reported to allow readers to evaluate how well the experimental model reflects natural exposure under field conditions. The examples by Greer & Collins (2007) and Garver et al (2011) include most of the necessary elements with the exception of Animal Ethics Committee approval of the experiment design. Research studies with amphibians and fish, but typically not molluscs and crustaceans, must be approved by the Animal Ethics Committee in most research institu-tions and should be reported as done in Purcell et al (2013), with the possible addition of approved protocol numbers (see Hyatt et al 2007).…”
Section: Explanationmentioning
confidence: 99%
See 2 more Smart Citations